PELAPORAN DAN ANALISIS BIAYA KUALITAS DALAM UPAYA PENGENDALIAN KUALITAS (Studi Kasus PT. Pacific Express Garment) - , NI MADE AYU CITRARASMI; , Bambang Riyanto L.S., Dr., M.B.A., CMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study are to identify, reclassify, and analyze the quality costs at PT. Pacific Express Garment into prevention costs, appraisal costs, internal failure costs, and external failure costs. Furthermore, reports of quality-related costs, analyze the quality costs, and evaluate problems related to the cost of quality which has the highest frequency of occurrence. Based on the survey results revealed that the prevention costs consists of quality planning, new-product review, training, process control, equipment maintenance, product-design verification, and other prevention cost